Libertà dei moderni, liberalismo e comunismo in Domenico Losurdo - Cantaro, Antonio (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2022)
This essay adheres to Domenico Losurdo’s idea that the communist movement should rethink critically the value of certain acquisitions of liberalism. As liberalism cannot be reduced to the apologetics of the cause of individual freedom, so communism cannot be reduced to the apologetics of the cause of social justice and equality. The downgrading of negative freedoms as libertas minor is in contrast with a practice that has always seen the Communists committed to their defence, to the point of sacrificing their lives. Communists have fought on the one hand, to denounce the dehumanization process consumed in liberal societies and, on the other, to universalize the promises of liberalism, by overcoming the exclusion clauses against the colonized people, the poor people and the women. Negative/Positive Freedoms; Exclusion Clauses: Liberalism; Communism.